2016 Lester Eastman Conference (LEC) 2016
DOI: 10.1109/lec.2016.7578933
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed power evaluation and simulation of high voltage 4H-SiC P-Type SGTOs

Abstract: Future Army pulsed power applications semiconductor devices that will meet requirements for highpower, low weight and volume, and fast switching speed. The following paper presents the pulsed power evaluation of high voltage silicon carbide (SiC) super gate turn-off (SGTO) thyristors. These devices are well suited for high voltage, high temperature pulsed power and continuous power electronic systems. A pulse-forming network (PFN) circuit and a low inductance, series resistor-capacitor (LRC) circuit were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Actually, the evidence on the turn-on propagation phenomenon of SiC GTO is also indirect in other experimental researches. It was believed that the electric field is unevenly distributed along the Gate Runner of SiC GTO and the cells (regions) closer to the Gate Pad were turned on firstly, and subsequently the on-state areas expanded gradually [14,15,32]. The damaged regions within the failured device after pulsed current experimental tests were observed to be near the Gate Pad.…”
Section: Discussion On Extremely Slow Current Rise Transientmentioning
confidence: 99%
See 4 more Smart Citations
“…Actually, the evidence on the turn-on propagation phenomenon of SiC GTO is also indirect in other experimental researches. It was believed that the electric field is unevenly distributed along the Gate Runner of SiC GTO and the cells (regions) closer to the Gate Pad were turned on firstly, and subsequently the on-state areas expanded gradually [14,15,32]. The damaged regions within the failured device after pulsed current experimental tests were observed to be near the Gate Pad.…”
Section: Discussion On Extremely Slow Current Rise Transientmentioning
confidence: 99%
“…However, several problems hinder the development of SiC GTO specifically for the pulse power applications. Firstly, the tested pulsed current waveforms of high‐voltage SiC GTO thyristors from both our homemade one and those fabricated by Cree Inc. have confirmed that there is one extremely slow current rise process during the initial current pulse stage, which greatly degrades the turn‐on performance and generates a large gap from the expected di/dt , but this phenomenon has been inadvertently ignored by researchers till now (see Figure 1) [4, 14, 15]. Secondly, the current crowding phenomenon during the turn‐on transient has greatly threatened the high‐stress robustness and long‐term reliability of SiC GTO under repetitive pulsed current conditions [16, 17].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations